Perceptions Of The Construction Professionals With Regards To The Safety Factors And Critical Safety Measures For The Enhancement Of Safety Performance On The Construction Sites In The Klang Valley - Ng, Yee Enn (2020)
The construction industry plays an important role in the aggregate economy in Malaysia and has contributed to the gross domestic product (GDP). Nevertheless, in line with the positive economic growth, the statistics show that the construction industry has higher fatality rates compared to other industries. The research aim and objectives of this research studies are to determine the perceptions of the construction professionals with regards to the most critical safety factor causing poor safety performance on the construction site in Klang Valley, to determine the perceptions of the construction professionals with regards to the relative importance of the critical safety measures to enhance safety performance on the construction site and to establish the method to improve safety performance on the construction site. A total of 10 critical safety factors and 10 critical safety measures for the enhancement of safety performance on the construction site were identified. Questionnaires were then designed and distributed to the construction professionals working in the respective construction companies located in Klang Valley. Pilot survey was conducted before the actual field survey. The collected data was analysed by using the Relative Importance Index (RII) and IBM-SPSS. The criticality of the safety factors and the relative importance of the critical safety measures perceived by the construction professionals was ranked based on the RII calculated. Cronbach’s Alpha reliability test was conducted using SPSS to measure the reliability of the questionnaire. The research findings show that ‘improper use or failure to use personal protective equipment (PPE) was the most critical safety causing poor safety performance and ‘increase safety awareness among construction workers’ was the most important critical safety measures to enhance safety performance on the construction site perceived by the construction professionals. The research findings have also implied that the effective ways to improve safety performance on the construction site are to increase compliance of construction workers to wear PPE on the job site and to promote safety awareness among the construction workers. This research study is useful for construction companies whereby the construction companies could focus on improving the safety performance on the construction site by planning and implementing effective actions to ensure PPE becomes a safety practice among the construction workers and increase the safety awareness among them.